Does Vincristine affect Cochlear function in children with acute lymphoblastic leukaemia? (Bangladesh Journal of Medicine, 2016)
Context: Vincristine chemotherapy has dose dependent ototoxicity. Early detection of ototoxicity is better with otoacoustic emissions and high frequency audiometry than conventional pure tone audiometry. The study was done to see if vincristine treatment interferes with hearing sensitivity in children.Methods and Material: A prospective study was conducted on twenty-three children with acute lymphoblastic leukemia (ALL) on Multi Center Protocol (MCP 841).These were subjected to conventional audiometry, high frequency audiometry and distortion product otoacoustic emissions (DPOAEs) before starting chemotherapy. The follow up audiological evaluation after early intensive phase chemotherapy (approximately 6 months) was conducted in thirteen children, who received 12 doses of vincristine (1.4 mg/m2), cranial irradiation of 1800cGy (>3 years) as per protocol and antibiotics as per clinical demands.Results: Baseline audiological evaluation was normal. Follow-up evaluation DPOAEs showed a declining tendency, however changes did not reach statistical significance. Differences in median hearing thresholds prior and post treatment in higher frequency audiometry were also minimal which was not statistically significant. Conventional audiometric thresholds were not altered.Conclusions: The reduction in the signal noise ratio of DPOAE, and reduced hearing sensitivity in high frequencies in post chemotherapy in comparison with baseline measures cannot be ignored though it has failed to reach the level of statistical significance. children on vincristine should have a pre chemotherapy and follow up audiological evaluation with DPOAE The results of the present study needs to be strengthened by including larger sample and long term follow up.Bangladesh J Medicine Jan 2016; 27(1) : 3-7